1958
DOI: 10.2172/4276982
|View full text |Cite
|
Sign up to set email alerts
|

A Gamma-Ray Attenuation Method for Void Fraction Determinations in Experimental Boiling Heat Transfer Test Facilities

Abstract: Gamma rays emanating from a radioactive source are beamed through and are attenuated by steam-water mixtures contained in a simulated reactor flow channel. The emergent radiation is detected by a scintillation crystalphotomultiplier tube assembly. An expression is developed which yields the void fraction when the detector output with the channel empty, filled with water, and containing the mixture in question, is known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1961
1961
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…In Ref. 20 The above formulation is permissible for small errors. However, when the errors become large it will produce error magnitudes that are not characteristic of the system.…”
mentioning
confidence: 99%
“…In Ref. 20 The above formulation is permissible for small errors. However, when the errors become large it will produce error magnitudes that are not characteristic of the system.…”
mentioning
confidence: 99%
“…Unfortunately, two-phase flow is neither stationary nor homogeneous. Effects due to lack of homogeneity in the form of parallel layers of gas and liquid oriented parallel to the photon beam were discussed by Hooker and Popper 48 and verified by Petrick and Swanson 86 who showed that errors as high as 40% could be possible. These errors are due to "photon streaming" preferentially through the gas such that the emergent attenuation is the sum of two separate exponentials rather than the exponential of the sum of two linear terms.…”
Section: A What Can Be Measured By Radiation Attenuationmentioning
confidence: 95%
“…According to the previously mentioned references, (19)(20)(21) the relation between the output signal i(t) of the current amplifier and the steam void fraction a(t) can be expressed as…”
Section: Chapter IV Gamma-ray Attenuation Methods Theorymentioning
confidence: 99%
“…It is known that the expectation value of an exponential is given by /exp z\ = exp(z + y a| ) (20) when z is Gaussian. From (20) …”
Section: Chapter IV Gamma-ray Attenuation Methods Theorymentioning
confidence: 99%